PENGARUH LIKUIDITAS, SOLVABILITAS, PROFITABILITAS, DAN GROWTH TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2020 (Menara Ilmu, 2022)
The purpose of this study is to determine the effect of liquidity, solvency, profitability and growth on dividend policy in manufacturing companies listed on the Indonesian stock exchange which are listed on the Indonesian stock exchange for the 2017-2020 period. This study was analyzed using multiple linear regression analysis. Based on the results of hypothesis testing, it shows that the F (simultaneous) test variables of liquidity, solvency, profitability and growth have an effect on dividend policy in manufacturing companies listed on the Indonesian stock exchange which are listed on the Indonesian stock exchange for the 2017-2020 period. And the results of the research partially only affect the profitability of dividend policy. Meanwhile, liquidity, solvency, and growth have no effect on dividend policy. The magnitude of this influence is 70.1%. while the remaining 28.9% is influenced by other factors outside the study.